ANALISIS MEKANISME IZIN PEMASANGAN REKLAME DIKANTOR PELAYANAN PERIZINAN TERPADU KOTA MEULABOH - Alimas Jonsa; Khairul Azwar (Universitas Teuku Umar, 2017)
The purpose of this research is to know the licensing mechanism to install billboards, to knowwhat constraints faced by the Office of Integrated Licensing Service (KPPT) in licensing to installbillboard and to know the strategy of supervision on the implementation of advertisement byKPPT in West Aceh regency. The method used in this research is descriptive research methodwith qualitative approach. Selection of informants in this study carried out by purposive samplingmethod is a technique of sampling data sources with certain considerations. The informants inthis study were Head of Program and Information (KPPT), Petitioner of License (Public),Regional Financial Management and Wealth Official (Additional Informant) and Satpol PP(Additional Informant) with total of informant ie 7 people who made sample in this research .Based on the results of research indicate that the service procedure at KPPT when viewed fromthe aspect of simplicity, clarity and certainty of requirements as well as details of retribution fee(Tax), legal certainty, responsibility, completeness of facilities and infrastructure and ease ofaccess. Obstacles faced by the KPPT, among others, due to the large number of people who takecare of the billboard permit and the society did not complete the requirements requested so thatthe process of issuing the permit to establish a billboard become obstructed. Strategy ofsupervision on the implementation of advertisements is to follow up unlicensed billboards.Keywords: Analicys, Installation Permit Mechanism Billboards, KPPT.